2009
DOI: 10.1177/0021955x08100045
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography-based Modeling of Structured Polymers

Abstract: A hybrid numerical-experimental approach is proposed to characterize the macroscopic mechanical behavior of structured polymers. The method is based on capturing the details of the material's microstructure using 3D X-ray Computed Tomography (CT). By employing segmentation and voxelconversion, the reconstructed volume is automatically converted into a finite element model that is subsequently used for mechanical analyses. The approach is demonstrated on a 2D polycarbonate (PC) honeycomb. An ideal representativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…However, in this study, a realistic structure is taken where the cells are randomly distributed, which is a result of their process history. Also, it should be mentioned that previous studies showed that the intrinsic material behavior strongly influences the effective mechanical behavior 9, 27, 28, 34. Plasticity causes localization in the structure, and therefore, one can anticipate that, by incorporating plasticity, larger models may be needed 10, 19, 34.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in this study, a realistic structure is taken where the cells are randomly distributed, which is a result of their process history. Also, it should be mentioned that previous studies showed that the intrinsic material behavior strongly influences the effective mechanical behavior 9, 27, 28, 34. Plasticity causes localization in the structure, and therefore, one can anticipate that, by incorporating plasticity, larger models may be needed 10, 19, 34.…”
Section: Discussionmentioning
confidence: 99%
“…To incorporate the effects of the complex structure of foams, finite element (FE) analyses have been used in many studies on foams and composites to determine the structure–property relationship 5, 9–20. In these studies, the artificially generated FE models were based on regular structures,5, 9–14 for example, perfect honeycomb structures and regular Kelvin cells, where others used irregular structures to more realistically represent the microstructure, mostly based on Voronoi tessellation 10, 11, 14–19. These studies conclude that small details of the foam morphology, like cell irregularity, cell wall thickness variations, and cell shape anisotropy strongly influence the mechanical responses of these structures.…”
Section: Introductionmentioning
confidence: 99%
“…The morphology of foam is characterised by the number and type of cell faces and the cross sectional area, shape and length of the cell edges. These characteristics were first quantified by the observations of (Matzke [3]) and were confirmed using (electron) microscopy (Gong et al [4], Mills [5]) and CTimaging more recently (Jang et al [6], Wismans et al [7]). In general, a cell with 14 faces and a face with 5 edges proved to be the most abundant.…”
Section: Introductionmentioning
confidence: 88%
“…From 2-dimensional interpolation formulations, the application on 3-dimensional cases can be easily derived using a bilinear patch Coons formulation. The finite element-based interpolation formulation, resulting in the so-called quasi-periodic boundary condition, was considered to apply the periodic boundary condition on a foamed RVE [63]. Finally, the master/slave approach [64] can be considered as a special case of finite element-based interpolation by considering directly the finite element mesh at the RVE boundary as interpolation bases.…”
Section: Interpolation-based Periodic Fluctuation Constraint Elementmentioning
confidence: 99%
“…Therefore, the interpolationbased periodic boundary condition is considered with the Coons patch formulation based on Lagrange or cubic spline interpolants [50] and with the finite elementbased formulation [63]. The obtained results are shown in Fig.…”
Section: Thermal Homogenizationmentioning
confidence: 99%